Reliability of intraocular lens power calculation after cataract surgery in patients with relative anterior microphthalmus - Bartke, Thomas; Auffarth, Gerd U.; Uhl, Jens C.; Völcker, Hans Eberhard (Graefe's archive for clinical and experimental ophthalmology, 2000)
Background: Patients with relative anterior microphthalmus (RAM) are characterized by special anatomical features (corneal diameters <11 mm, anterior chamber depth <2 mm and normal axial length) that sometimes make intraocular lens (IOL) power calculation difficult. · Patients and methods: Seventy-five patients aged 75.6±10.3 years with RAM were evaluated for preoperative target refraction and postoperative refraction after cataract surgery. We used biometric formulas as modified by Haigis for IOL power calculation. · Results: The average IOL power implanted was 25.2±2.8 dptr (one-piece all-PMMA IOL; range 19-31 dptr). The preoperatively calculated target refraction was -0.71±1.43 dptr (range -4.3 to +2.2 dptr). The average postoperative spherical equivalent was -0.41±1.50 dptr (range -5.5 to +6.0 dptr). The mean difference between target and end refraction was -0.30±1.54 dptr Fifty-seven percent of cases did not differ by more than 1 dptr from target refraction, 81.3% by not more than 2 dptr, and 94.7% by not more than 3 dptr; only 5.3% of cases deviated by more than 3 dptr. There was no correlation of the amount of deviation between target and postoperative refraction with axial length, corneal diameter and anterior chamber depth. There was, however, a significant correlation between target refraction and amount of deviation of spherical equivalent. The largest differences were found with target refractions greater than +2 dptr. · Conclusions: In spite of the special anatomical conditions in patients with RAM the biometric formulas as modified by Haigis produced reliable IOL power calculations. The best accuracy was achieved when aiming at a target refraction in the range of ±2 dptr.